Managemental Competencies in the performance of nurses in Private Hospital: a study of multiple case - Luciane Filgueiras Cadete Caramez; Zenith Rosa Silvino (Online Brazilian Journal of Nursing, 2009)
This is a research project of Professional Master in Nursing Program, School of Nursing, Federal Fluminense University. Qualitative research that uses as strategy multiple case study. Search to describe management responsibilities required by the hospital and search analyses on the relation between the responsibilities and the work developed by nurse management. The research scenario will be made by the private health system of Volta Redonda, RJ, Brazil. The subjects will be the principals of hospitals /nursing homes and head nurses within their respective hospitals. For analyses will be used Alceste 4 software 4.9 version.